Immigrant Satisfaction: What Is It? Does it matter? - Lester, L.H (My University, 2005)
This Working Paper examines the relationship between immigrant’s self-reported satisfaction and other variables available in the Longitudinal Survey of Immigrants to Australia (LSIA) using (exploratory) cross-tabulation tables. There have been two LSIA, selected from off-shore visaed immigrants (with permanent resident status), and their migrating unit family where appropriate (\DIMIA, 2002 #132}. The first cohort (LSIA1) arrived in Australia between 1st September 1993 and 31st August 1995. This cohort was interviewed on three occasions, approximately five to six months after arrival (wave 1), after a further 12 months (wave 2) and a further two years later (wave 3).
Working Paper No 154
Keywords: Life Events -- Immigration / newly arrived migrants; Satisfaction; Surveys and Survey Methodology -- Survey response; Surveys and Survey Methodology; Disadvantage, adversity and resilience; Surveys and survey methodology; Satisfaction; Life Events; Surveys and Survey Methodology; Survey response; Immigration / newly arrived migrants; Adversity and resilience; Surveys and Survey Methodology; Dsiadvantage, adversity and resilience